Changes in Psp protein binding partners, localization and behaviour upon activation of the Yersinia enterocolitica phage shock protein response. Issue 3 (7th January 2013) - Yamaguchi, Saori; Reid, Dylan A.; Rothenberg, Eli; Darwin, Andrew J.
Summary PspA, ‐B and ‐C regulate the bacterial phage shock protein stress response by controlling the PspF transcription factor. Here, we have developed complementary approaches to study the behaviour of these proteins at their endogenous levels in Yersinia enterocolitica. First, we observed GFP‐tagged versions with an approach that resolves individual protein complexes in live cells. This revealed that PspA, ‐B and ‐C share common behaviours, including a striking contrast before and after induction. In uninduced cells, PspA, ‐B and ‐C were highly mobile and widely distributed. However, induction reduced mobility and the proteins became more organized. Combining mCherry‐ and GFP‐tagged proteins also revealed that PspA colocalizes with PspB and PspC into large stationary foci, often located close to the pole of induced cells. In addition, co‐immunoprecipitation assays provided the first direct evidence supporting the model that PspA switches binding partners from PspF to PspBC upon induction. Together, these data suggest that PspA, ‐B and ‐C do not stably interact and are highly mobile before induction, perhaps sampling the status of the membrane and each other. However, an inducing signal promotes PspABC complex formation and their relocation to discrete parts of the membrane, which might then be important for mitigating envelope stress.